El metabolismo acido de las crasulaceae: diversidad , fisiologia ambiental y productividad - Andrade, J.L.=700 1 De la Barrera, E.; Reyes Garcia, C.; Ricalde, M.F.; Vargas Soto, G.
(En, Es)
ilus., 127 ref.
Keywords: CRAáULACEAE; CICLO CAM; METABOLISMO ENERGETICO; EPIFITAS; MEDIO AMBIENTE; PRODUCTIVIDAD; ISOTOPOS; MEXICO